Genome-wide identification of signatures of positive selection in African admixed zebu cattle - Bahbahani, Hussain (2015)
The small East African shorthorn zebu (EASZ) is an indigenous stable zebu x taurine admixed cattle population highly adapted to the local African environment, i.e. disease resistance, thermotolerance, sustain themselves on poor feed quality, in comparison to the exotic productive cattle. Understanding the genetic control of their adaptations will help sustainable breeding improvement programs, both within populations and through crossbreeding. In this thesis, genome-wide SNP data, from two commercially available SNP arrays; the Illumina BovineSNP50 BeadChip v.1 and the Illumina BovineHD BeadChip, and full genome sequence of 10 pooled EASZ samples were used to define candidate regions with signatures of positive selection in the genome of EASZ. In chapter 2, the low-density SNP chip has defined 24 candidate regions (21 in the autosomes and three in the sex chromosome X (BTA X) by two Extended Haplotype Homozygosity (EHH)-based (intra-population iHS and inter-population Rsb) analyses and an inter-population FST approach. Characterising the EASZ genome with high-density genome-wide SNP analyses (meta-SS, Rsb, iHS and ΔAF) and pooled heterozygosity (Hp) sequence analysis, in chapters 3 and 4, identified a total of 266 autosomal and 20 BTA X candidate regions. Analysing genome-wide SNP data of zebu cattle populations from Uganda and Nigeria classified some of these regions as East African zebu-sharing and East and West African zebu-sharing candidate regions. Genes and quantitative trait loci (QTL) associated with adaptive traits (e.g., reproduction, immunity and heat stress) were found within the identified candidate regions. Moreover, Nine non-synonymous variants were found in five candidate genes and considered as possible causative mutations under selection. Finally, the mitochondrial DNA (mtDNA) of 13 EASZ were investigated and affiliated to T1a, T1b and T1b1 sub-haplogroups. No selective advantage was found to be associated with taurine mtDNA over the zebu type. Although purifying selection is the main selective factor influencing African cattle mtDNA, in Cox-2 gene of the T1b/ T1b1 sub-haplogroups a non-synonymous mutation may confer a selective advantage. The results of this thesis are just the first milestone to define the valuable genetic material in EASZ, which should be conserved in future composite cattle upon informed selective crossbreeding and/or the recently introduced gene modification techniques (TALEN and CRISPER/Cas9).